Factors influencing business performers in bandung to adopt cloud based pos and features influencing business owners’ preferences in choosing pos provider – empirical evidence from the utaut model - Geovanno, David Ezra Michael; Koesrindartoto, Deddy Priatmodjo (Journal of Business and Management, 2019)
Implementation of information technology is essential for the company, because it can increase the effectiveness and efficiency of the company performance. In the era of massive technology development, businesses are in a race to retain customer loyalty and attract potential customers by applying an appropriate technology within their business process. In this study, the researcher is eager to describe how the micro small and medium enterprises (MSMEs) business survive by the assist of technology so called the Point of Sale (POS) system. Recently the POS has evolved as one of the financial technology (Fin-Tech) that’s becoming very essential in order to support its activity in a quick and integrate work process. The POS has the basic function of record transaction, but unlike conventional cash register, it is now having the capability of storing data in cloud-server that integrate all the aspects within a business environments starting from payment and even supplier management. The researcher then tried to recognize the factors that significantly affect the technology adoption applying the UTAUT research model that consists of four determinant variables of performance expectancy (PE), Effort Expectancy (EE), Social Influence (SI), and Facilitating conditions (FC) all as latent variables that could affect the Behavioral Intention (BI) of the technology. The later finding then reveals that how the performance expectancy (PE) and social influence (SI) drive the intention of the cloud-based system through Partial Least Square (PLS) statistical method using SmartPLS 3.0. In addition, the research also elaborates the features of existing cloud-based POS providers in the country and compare their functional features and how they could deliver or introduce it to the market and increase their user volume. The comparison matrix of the five POS providers eventually reveals that a completeness of features does not significantly affect the business preference.